2018
DOI: 10.2174/1570161115666171010123157
|View full text |Cite
|
Sign up to set email alerts
|

Association between Apolipoproteins AI and B and Ultrasound Indicators of Carotid Atherosclerosis

Abstract: Among RFs and their biomarkers, apoA-I, apoB and the apoB/apoA-I ratio showed strong association with ultrasound indicators of carotid atherosclerosis in IS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“… 7 Therefore, the ApoB/ApoA-I ratio may be better indicators of the risk of subclinical atherosclerosis and better therapeutic targets for reducing the risk of plaque formation and cerebrovascular disease. 29 , 30 However, our study found that ApoA-I levels were significantly higher in patients with CAS than control participants and associated with a 5.4 fold increase risk of CAS. Besides, ApoA-I plasma levels were not affected by the ApoE polymorphism.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“… 7 Therefore, the ApoB/ApoA-I ratio may be better indicators of the risk of subclinical atherosclerosis and better therapeutic targets for reducing the risk of plaque formation and cerebrovascular disease. 29 , 30 However, our study found that ApoA-I levels were significantly higher in patients with CAS than control participants and associated with a 5.4 fold increase risk of CAS. Besides, ApoA-I plasma levels were not affected by the ApoE polymorphism.…”
Section: Discussioncontrasting
confidence: 58%
“…Zivanovic et al and Jun et al showed that high levels of ApoB and ApoB/ApoA-I ratio were significantly associated with CAS. 29 , 30 ApoE protein is synthesized in the liver and macrophages, and it plays a crucial role in antiatherogenic properties by regulating regulating lipid and lipoprotein metabolism. 31 The present study showed that ApoE levels were significantly depleted in the CAS group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As a chronic inflammatory disorder of the arterial vessel wall, atherosclerosis is one of the leading causes of death worldwide 23 . Multiple risk factors have been identified, including hyperlipoproteinemia, hypertension, diabetes, obesity, and smoking 24 . At present, Hcy is considered an independent risk factor of atherosclerosis 25 .…”
Section: Resultsmentioning
confidence: 99%
“… 26 Based on other reports, in addition to the common factors such as LDL-c and HDL-c, ApoB and ApoA 1 may be better indicators of the risk of cardiovascular and cerebrovascular diseases compared with conventional risk factors. 27 , 28 A meta-analysis 29 also indicated that ApoB is a more accurate marker of cardiovascular risk compared with LDL-c. Through screening by univariate and multivariate logistic regression, our study showed that ApoB levels are associated with a higher incidence of IS compared with TG, TC, and LDL-c, and that ApoA 1 is negatively correlated with the onset of IS.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ApoB has become an important indicator for predicting the incidence of IS, and most current studies focus on the prediction risk for acute IS. 26 29 Our article further analyzes the follow-up data from stroke survivors who were treated with clopidogrel. Compared with other blood lipid variables, ApoB has a certain significance in predicting IS recurrence.…”
Section: Discussionmentioning
confidence: 99%